Pengaruh Profitabilitas, Likuiditas, Leverage, dan Corpo-Rate Governance Terhadap Kecurangan Laporan Keuangan, Serta Financial Distress Sebagai Variabel Intervening - Albert Adi Nugroho; Zaki Baridwan; Endang Mardiati (Trunojoyo University of Madura, 2018)
This paper examines the affect of profitability, liquidity, leverage, and corporate governance to financial statement fraud, and financial distress as a intervening variable. Based on Association of Certified Fraud Examiners (ACFE) 2016, financial statement fraud was growth from 2012 – 2016, it’s mean more companies have a motivated to do manipulate financial statement. In this paper, financial distress as a intervening variable before companies manipulate financial statement. We conclude profitability, leverage, shareholding, number of boards are significant to financial distress. Finally financial distress is significant to financial statement fraud